Wissensbasierte und berechnungsunterstützte Konzeptabsicherung in den frühen Phasen der Produktentwicklung am Beispiel des Elektromotors - Tüchsen, Johann; Richter, Michael; Heydenreich, Johannes; Koch, Matthias; Schleich, Benjamin; Wartzack, Sandro (2018)
In order to prevent costs and unneeded effort in product development, design verifications in early development phases are used to identify non-suitable designs and errors. Therefore, this contribution proposes a concept for a completely automated design check based on simplified one-dimensional calculations including knowledge-based correction factors optimized for electric drives. Using knowledge-based systems (KBS) structure in combination with compiled template computer scripts, a very fast and multidisciplinary solution is given to evaluate the suitability of the created solution regarding the requirements. Additionally this concept is expandable for additional modules or motors and easy to maintai
Keywords: Konzeptabsicherung; Knowledge-based Systems; KBS; analytische Modelle